Evaluation of Boundary-Spanning on Climate Change ENGO International Greenpeace in Asia - Genta Mahardhika Rozalinna; Aulia Izzah Azmi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This paper discusses the evaluation of boundary-spanning on climate change ENGO International Greenpeace in Asia. The evaluation process uses secondary data from documents presented on the official website of Greenpeace, especially countries in Asia. These countries include Indonesia, Malaysia, the Philippines, Thailand, India, Japan, South Korea, and China. Evaluation of the boundary-spanning is obtained from the results of the mapping of all issues and campaigns related to climate change. The results: 1) limitation of the problem and identity of the campaigns carried out out all based on the ecological conditions of each country; 2) limitation organizational through institutional strengthening becomes the main focus in the pattern of movement, and tactical efforts are made through the publication of reports and analysis is step by step in various communication and action media.